Analisis Yuridis Pembinaan Residivis Anak Pada Lembaga Pemasyarakatan Khusus Anak - Aryani, Gustina; Nadriana, Lenny; Arum, Ratna (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2023)
The development of prisoners in Indonesia is implemented in the correctional system. Various forms of guidance for correctional students at Special Child Development Institutions cannot be separated from a change in the correctional system, which aims to provide provisions for correctional students to face life after completing their sentence. The problems that will be examined in this article include how to foster child recidivism in Special Child Development Institutions and what are the inhibiting factors in the implementation of child recidivism guidance in Special Child Development Institutions. The method used in this research is Normative Juridical and Empirical Juridical Research Methods, using primary data and secondary data. Research Results: The Bandar Lampung Special Children's Development Institute has generally attempted to provide rights to children by implementing and providing guidance in accordance with what is mandated by law. The implementation of coaching for correctional students who are recidivists has so far been the same as other correctional students who are not recidivists, this is because the program and coaching patterns that have existed so far have regulated this. In its implementation, Special Child Development Institutions find it quite difficult to run a coaching program, several inhibiting factors in the implementation of recidivist coaching for correctional students include: low level of education, children's skill abilities, lack of community participation and children's changing thinking patterns. Suggestions that can be given by the author regarding the problems that arise include: for Special Child Development Institutions, it is necessary to differentiate between the training of ordinary correctional students and recidivist correctional students which can have a deterrent effect on children so that they do not commit crimes again, for example by developing their mental health. children and put more emphasis on spiritual development and for officers at Special Education Institutions for Children to be able to encourage correctional students not to commit criminal acts again.